KONFLIK SOSIAL DALAM KOMUNITAS VIRTUAL DI KALANGAN REMAJA - Alfredo Elrio Elrio; Edy Soesanto, Fadzell Auraffa Ahmad, Fathan Abdullah Putranto (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Humans are social creatures who really need interaction with each other in their lives. The presence of virtual communities makes interaction between individuals and groups easier. Any kind of interaction, whether in the form of production, distribution and consumption of messages in a virtual community, has the potential to cause conflict. Social conflict is conflict between members of society, in this case the object is teenagers. The presence of this virtual community is also a center for disseminating information and hoaxes (Fake Information) which can cause conflict in virtual communities among teenagers. This research aims to investigate the causes of conflict in virtual communities and how to resolve them. This research uses a qualitative approach. Data was collected through online participation, interviews, documentation and literature studies relevant to this research. This research found that social conflict in virtual communities among teenagers is caused by misunderstandings in understanding texts or opinions, sensitivity to symbols, time and function of the community, cyberbullying, posting about SARA issues and, egoism regarding the different backgrounds of members in the community. This conflict divided virtual community members into three groups, namely conservatives, liberals and silent readers. There are several ways to resolve virtual conflicts that occur, including conciliation between conflict actors, mediation, changing the conversation or sending pictures that can invite laughter from other members.